KEMAMPUAN KOMPONEN ARUS KAS METODE LANGSUNG DALAM MEMPREDIKSI TOTAL KAS OPERASI MASA MENDATANG - Indah Purwati; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2014)
The study aims to examine the predictive ability of components operating cash flow method to future cash flows. Based on the Farshadfar and Monem, is proposed direct cash flow method components model to predict future operating cash flow and predict control analysis for different industry type (industrial base and chemical, Other industry, customer good). Using secondary data processing for manufacture and regression-path analysis. Indirect cash flow components method (cash received from customers, cash paid to suppliers and employees, net interest paid, taxes paid, other cash flows from operations) are collectively analyzed to prdictive operating cash flow. The test results in the study show that cash received from customers, cash paid to suppliers and employees, net interest paid, other cash flows from operations are significaly effect to 1 year until 4 years future cash flow prediction. The taxes paid is significaly effect to 1 year predict, and it’s not significaly effect to 2 until 4 years prediction. control analysis find that cash prediction is higher for customer good than the other industry type. The positive cash flow better to predict future cash flow than negative cash flow.